2020
DOI: 10.2298/tsci2006923y
|View full text |Cite
|
Sign up to set email alerts
|

On distribution characteristics of the temperature field and gas seepage law of coal in deep mining

Abstract: The study of gas seepage under the condition of multifield coupling has always been an important topic in coal mining. Based on the theory of multifield coupling and the research method of numerical simulation, the influences of the stress and temperature fields on the seepage field under the conditions of deep coal mining are studied. With the example of the J15-31030 deep working face from mine No. 12 in the Pingdingshan Coal Mine, modeling and finite element analysis are carried out. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Qu et al 28 investigated the stability of rock slope under the stress-seepage-temperature-chemical coupling condition and obtained the parameter change rules including stress, temperature, deformation, and damage. Yang et al 29 analyzed the influences of the stress and temperature fields on the seepage field under the deep coal mining condition and revealed that the temperature field has a significant influence on the adsorbed gas in the seepage field.…”
Section: Introductionmentioning
confidence: 99%
“…Qu et al 28 investigated the stability of rock slope under the stress-seepage-temperature-chemical coupling condition and obtained the parameter change rules including stress, temperature, deformation, and damage. Yang et al 29 analyzed the influences of the stress and temperature fields on the seepage field under the deep coal mining condition and revealed that the temperature field has a significant influence on the adsorbed gas in the seepage field.…”
Section: Introductionmentioning
confidence: 99%
“…Coal is the dominant energy source in China, and it is expected to account for more than 50% of primary energy consumption by 2030, and coal will remain the basic energy to ensure China's energy security and stability [1,2]. China's main coal mining is underground mining method, and with the increase of mining depth, the risk of coal and gas protrusion increases [3][4][5][6][7]. To effectively control coal and gas outburst accidents, the national bureau of coal-mine safety issued Prevention and Control of Coal and Gas Outburst Conditions [8], emphasizing the prominent danger zone with the conditions of mining the protective layer, and mining the upper protective layer as a priority.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the gas pressure and gas content in coal seam also increase. All the factors interact and influence each other, and the gas disaster becomes more and more serious [2][3][4]. e traditional protective layer mining method of the coal seam encounters great challenges.…”
Section: Introductionmentioning
confidence: 99%